Explicit Verbal Irony and the Means of Marking It in the Journalistic Style of the Serbian and Croatian Languages. - Karlić, Virna; Koletić, Goran (Zeitschrift für Balkanologie, 2013)
The paper explores explicit and intentional verbal irony, with particular focus on determining the means of marking it in the journalistic style of the Serbian and Croatian languages. The first part examines the difficulties with regard to providing a general definition of verbal irony, its characteristics and typology as related to the means and media of its expression. The central part of the paper involves the identification of irony markers in Serbian and Croatian through analyzing the content of magazine articles.